The modernist Mirk Shah method and sources in his commentary on the book of the merits of Imam Tirmidhi - al - Habradi, Hadi bin Qaad Hadi (Journal of Humanities & Social Sciences, 2017)
A number of modernists have emerged in the city of Herat, and this city is now located in Afghanistan, where these modernists lived under the Safavid rule. Some of them were killed, including Hajar. Several scholars of the city, Mullah Ali Qari, , And made great efforts in the service of the Prophet's biography and still their books traded students of science between study and investigation. The study aims to explain the approach of modernist Nasimuddin Mirk Shah, and show his dealings with the ahaadeeth, the strangest Arabic language, the method of his transfer from the scholars and his meditations, and the diversity of his sources' which indicate his knowledge and culture. In the book of Shamal Imam Tirmidhi, who is a mayor in his door, and the results reached by the study: the acceptance of God's book of the good Tirmidhi, Where scientists dealt with the explanation, and To fine tune, translation ... etc., and also encyclopedic updated Merck Shah, and it clearly shows how the sources relied upon, the art of subtraction of the author in the presentation and rebuttal information.
Keywords: Al-Sharh; Al-Shamael; Merck; Herat; Method